Examining the Role of Motivation in the Effect of the Make-a-Match Model on Students’ Academic Performance - Dhika Nusratul Janah; Iskandar; Rani Tania Pratiwi (THE PRESTISE, 2025)
The background of this research is the low learning outcomes of Grade X students in economics, with many students scoring below the predetermined minimum competency criteria (KKM). This study aims to determine and describe: (1) the effect of the Make a match type cooperative learning model on students' learning outcomes, (2) the effect of learning motivation on students' learning outcomes, and (3) the interaction effect between the Make a match type cooperative learning model and learning motivation on students' learning outcomes.The research method used is quasi-experimental with a 2x3 factorial design. The variables in this study include the Make a match type cooperative learning model as the independent variable, learning outcomes as the dependent variable, and learning motivation as the moderating variable. The research subjects were students of Class X-11 (experimental class) with 35 students and Class X-10 (control class) with 35 students. The instruments used in this study were multiple-choice tests and questionnaires to assess students’ learning motivation. The data analysis techniques used were normality test, homogeneity test, and hypothesis testing (Two-Way ANOVA).The results of the study indicate that: (1) there is a positive effect of the Make a match type cooperative learning model on students' learning outcomes, (2) there is a positive effect of learning motivation on students' learning outcomes, and (3) there is an interaction effect between the Make a match type cooperative learning model and learning motivation on students' learning outcomes.